ANALISIS ASPEK STRUKTUR BIROKRASI YANG BERLANGSUNG PADA PROGRAM KELAS IBU BALITA DI WILAYAH KABUPATEN BANYUMAS - Pantiawati, Ika (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Analysis of the Aspects of Bureaucratic Structures Underway in the Toddler Class Program in Banyumas Regency. The mother-to-child class is a class where mothers with children aged between 0 and 5 years together discuss, exchange opinions, exchange experiences with health services, nutrition and stimulation of growth and development are guided by facilitators, in this case using MCH books. Under-fives motherhood program was socialized in Banyumas district in 2011, but from 331 village midwives no one has been trained as a toddler classroom facilitator. The purpose of this study is to analyze the aspects of bureaucracy strktur that is going on in the Toddler Class Program in Banyumas Regency. This research used observational design with qualitative approach. Key informants were selected based on active and inactive motherhood classes and achievement of toddler-grade maternal outcomes. Key informants 13 village midwives, informants triangulation are 4 midwives coordinator, 1 Sie KIA Banyumas District Health Office and 10 mothers of the toddler mothers class. Data were collected by in-depth interviews and FGDs. Processing and data analysis using content analysis. The result of the analysis of the implementation of maternal-toddler classes from the active and non-atif mother-age classes is still not good, the bureaucratic structure is still much not seen yet. Bureaucracy structure: unavailability of SOP. Keywords: Bureaucracy Structure, Toddler Class Program